Peningkatan Kualitas Pembelajaran Melalui Penerapan Paktek Laboratorium Mata Kuliah Keperawatan Anak - Teresia Elfi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Learning planning is a design or preparation made by a lecturer regarding learning which is his responsibility before carrying out learning, including making a skills lab learning design. The results of a preliminary study at the Nursing Undergraduate Study Program, Faculty of Health Sciences, University of Nusa Nipa in planning the learning of child nursing lab skills, still found several problems, namely in the analysis of the learner and the environment and the Semester Learning Plan (SLP) which had not been maximally available and planned. This can affect the implementation of laboratory learning (skill lab) which is less than optimal and in the end the competence of students is not achieved (Depkes RI, 2000). This study aims to describe the picture of improving the quality of learning through the implementation of learning planning in the Child Nursing Lab skills in the Bachelor of Nursing Study Program, Faculty of Health Sciences, University of Nusa Nipa. This research was conducted using a qualitative descriptive research type with embedded case study research. Data collection techniques were carried out by means of in-depth interviews and participatory observation through focus group discussions. The research population was 34 students in Semester V nursing undergraduate students at Nusa Nipa University for the academic year 2020/2021. Sampling using total sampling. Data processing was carried out by means of descriptive content (content analysis) using an interactive analysis model which included data collection, data reduction, data presentation and verification/drawing conclusions. The results of the study showed that there was an increase in the quality of learning through the implementation of learning planning in the Child Nursing skills lab according to the SLP and there was already a practicum guidebook in the form of SOP (Standard Operating Procedure) and Semester Learning Plan (SLP). The conclusion of the lesson plan for child nursing lab skills in the Bachelor of Nursing Study Program, Faculty of Health Sciences, University of Nusa Nipa, has been well planned in a structured manner and has been well implemented.